The Relationships Between Social Justice Leadership and Organizational Commitment - Fazi, Faizulhaq (Journal of Social Sciences - Kabul University, 2024)
This research aims to examine the relationship between social justice leadership and organizational commitment, and it is a quantitative survey-correlation study. The statistical population consisted of teachers from the third district of Kabul city, from which 405 teachers were randomly selected as the sample. The data collection instrument was a questionnaire with a Cronbach's alpha value of 0.86. The data was analyzed using the SPSS software version 25, employing descriptive and inferential statistics. The Mann-Whitney, Kruskal-Wallis, Spearman, and multiple linear regression tests were applied to test the hypotheses. The most important findings indicated a positive and significant correlation between social justice leadership and organizational commitment and that social justice leadership can also affect teachers' organizational commitment. This research demonstrates how leadership based on social justice can enhance organizational commitment, thereby improving teachers' productivity and job satisfaction.